ANTHROPOLOGIST AND GOVERNMENT EMPLOYEE: A DESCRIPTION OF CAREER PATHS TO BECOMING AN APPLIED ANTHROPOLOGIST WITH THE U.S. DEPARTMENT OF VETERAN AFFAIRS. Issue 2 (November 2013) - Fix, Gemmae M.; Besterman‐Dahan, Karen; Hamilton, Alison
<x xml:space="preserve">Abstract</x> The U.S. government is the largest employer of anthropologists, with an increasing presence in the Department of Veteran Affairs (VA). However, there has been limited discussion of the path from graduate school to an applied career. This article describes the motivations and trajectories of anthropologists employed by VA. Interviewees described their VA work as embodying the principles of anthropology and the ability to see the results of their work as deeply gratifying.